Physiological, perceived, and physical demands of recreational 3×3 basketball and high-intensity interval training in sedentary adult women - Golluceli, Berk; Kamandulis, Sigitas; Pernigoni, Marco; Lukonaitiene, Inga; Kreivyte, Rasa; Conte, Daniele (Biology of Sport, 2025)
The aim of this investigation was to compare the acute physiological responses – percentage of maximal peak heart rate (%HRpeak) and blood lactate (BLa) – as well as perceived demands (rating of perceived exertion, RPE) and enjoyment of a recreational 3×3 basketball match and high-intensity interval training (HIIT) in sedentary women. Twelve healthy, adult sedentary women (age: 37±14 years; body mass: 66 ± 19 kg; stature: 162 ± 13 cm; fat mass: 27.5 ± 12.5%) performed a 3× 3 basketball match and HIIT including gym-based activities with comparable duration. The %HRpeak was continuously monitored during, the BLa was assessed before and after, and the RPE and enjoyment were collected at the end of each protocol. 3×3 basketball elicited higher %HRpeak ( p < 0.001; d = -1.64, large). BLa analysis demonstrated a significant difference for all the between- and within-condition comparisons ( p < 0.05; r-values: large) except for the comparison between pre-HIIT and pre-3×3 basketball match ( p > 0.05; r-value: 0.052, no effect) and between post-HIIT and post-3×3 basketball match ( p = 0.072; r-value: 0.495, medium). Similar low RPE (4±1 AU; p = 0.999; r-value = < 0.001, no effect) and high enjoyment (3×3 basketball = 6±1 AU; HIIT = 5AU±1 AU, p = 0.233; r value = 0.250, small) values were found between conditions. 3×3 basketball induced overall higher %HRpeak compared to HIIT, suggesting its suitability as a health-enhancing activity for sedentary adult women. Moreover, since both conditions highlighted low RPE and high enjoyment values, they have the potential to be effective in enhancing the training adherence in sedentary adult women.